PENGARUH IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA BANK YANG TERDAFTAR DI BURSA EFEK INDONASIA - Rafika, Indah; Husaini, Husaini; Sari, Novita (UNIB Press, 2020)
The purpose of this study is to examine the effect of good corporate governance (GCG) on earnings management of Indonesian banks that listed in Indonesia Stock Exchange. The GCG in this study is proxied by independent commissioners, board of commisioner size, audit committee, and audit reputation. The earnings management as measured by major accruals in the banking sector, namely Loan Loss Provisions (LLP). The sample in this study was 39 indonesian banks that listed on the Indonesia Stock Exchange for the period 2014-2018. The results show that board size has a negative effect on earnings management. On the other hand, independent commissioners, audit committees, and auditors' reputation have no effect on earnings management.